Ultrahigh-Speed Near-Infrared Electrodynamic Solid-State Trans-Memory - Kumar, Mohit; Seo, Hyungtak (ACS Applied Electronic Materials, 2022)
Emerging information technology necessitates the well-controlled manipulation of light transmission while maintaining memory behavior; therefore, achieving dynamic optical properties of a solid-state material is crucial. However, despite the vital role of solid-state architecture in photonic sensors, communication, and memory storage, the realization of adjustable optical transmittance across a thin film remains a challenging task, since it is primarily governed by intrinsic material stoichiometry. Here, we developed a proof-of-concept solid-state copper oxide-based device in which optical transmittance, particularly the near-infrared range, can alert reversibly in various levels, ranging from 76 to 36%, by fine-tuning short (∼1 ms) electric pulses. The device maintained its flipped transmittance value even when the illumination intensity remained constant, offering nonvolatile multilevel memory. Current-Voltage curves show a stable analog hysteresis loop opening, and based on the valence band spectroscopy measurement, the underlying working mechanism is explained by the kinetics of oxygen vacancy migration-induced change in the stoichiometry of copper oxide. Furthermore, an array was built and trained to transmit the well-controlled optical intensity over a selective area. Tuning the optical property with an electric field opens an avenue for the development of reconfigurable thin-film-based area-selective optical devices for a variety of applications, including display, optical window, and electrooptical coatings.
Keywords: Controlled manipulations; Dynamic optical property; Emerging information technologies; Near Infrared; Near-infrared; Nonvoltaic; Thin-films; Tunable transmittance; Tunables; Ultra high speed; electrodynamic; near infrared; nonvoltaic; tunable transmittance; ultrahigh speed